BLOOM TAXONOMY USED BY TEACHER IN LESSON PLAN - Roza Susanti; Dwi Settya Mahaputri (Universitas Mahaputra Muhammad Yamin, 2022)
Taxonomies used in education are referred to as following Bloom's Taxonomy. This study examines the use of Bloom's Taxonomy in the English teacher's lesson plans at the senior high school in East Payakumbuh. Descriptive research is what this study fell under. East Payakumbuh Senior High School served as the research setting. Th participants included English teachers from grades X and XI. As a source of information, the researcher studied official documents. Peer debriefing was employed by the researcher to verify the reliability of the data. The researcher followed the steps Gay suggested for data analysis. There were a few procedures involved in analyzing the descriptive data, including data data managing, reading or memoing, description, classifying, and writing report (2003:239). According to the findings, the English teacher used the cognitive domain the most in lesson plans, specifically C1 (Knowledge) 110 times; the affective domains were A2 (Responding) 6 times; and the psychomotor domains were P3 (Precision) 37 times.